Calculating State Economic Losses Through GDP Indicators: Toward Severe Punishment Based on the Principle of Justice - Ulil Amri; Amir Ilyas; M. Syukri Akub; Muhammad Mutawalli Mukhlis; Mohamed W. Abouyounes (Nusantara: Journal of Law Studies, 2026)
Corruption causing state economic losses in Indonesia has become increasingly systemic and has generated substantial disparities in criminal sentencing over the last five years. These disparities are closely related to the absence of measurable sentencing standards and to inconsistent judicial interpretations of the calculation of state economic losses, despite the Constitutional Court’s requirement that such losses be concrete and quantifiable. This study aims to analyze state economic losses in corruption cases through the perspective of economic analysis of law and to formulate a justice-oriented framework for severe punishment based on Gross Domestic Product (GDP) indicators. This research employs a normative juridical method, drawing on statutory, conceptual, and case approaches. Legal materials were obtained from legislation, court decisions, legal doctrines, and relevant economic theories. The data were analyzed qualitatively using an economic analysis of law framework emphasizing proportionality, deterrence, efficiency, and protection of public welfare. The results of this study indicate that sentencing disparities primarily stem from the lack of standardized economic parameters for assessing the broader impact of corruption on national development and social welfare. The study finds that judicial consideration has generally focused only on direct financial losses, while indirect economic consequences, including opportunity costs, disruption of public services, decline in investment, and multiplier effects on economic growth, remain insufficiently addressed. The results further demonstrate that integrating explicit and implicit economic losses through GDP indicators provides a more objective and proportional basis for determining criminal sanctions. This study formulates a GDP-based sentencing matrix by measuring the ratio between total state economic losses and annual GDP as an indicator of macroeconomic harm. The study concludes that corruption causing extraordinary economic disruption justifies severe punishment, including life imprisonment and capital punishment, under the principle of justice.